Inovasi Pembelajaran Agama Melalui Pembuatan Modul Ajar Bagi Anak di Dusun Prayungan Desa Kuwik Kecamatan Kunjang - Zaeni, Abu; Amalia Sa’adatul Chusnaini; Badiatul Faizah; Nur Fa’an Alifatul Maula (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
Education is a crucial process for forming understanding, maturity and critical thinking abilities in humans. In Indonesia, education is divided into three main channels: formal, non-formal and informal. Informal education, provided in the family environment before school, is an important basis. Non-formal education, such as the Al-Qur'an Education Park (TPQ), functions to complement and deepen formal education with an emphasis on developing students' potential and knowledge. TPQ plays an important role in instilling religious values ​​from an early age through teaching the Koran and religious materials. To increase the effectiveness of learning at TPQ, structured teaching modules are needed, which facilitate teaching and learning and ensure consistency and quality. Teaching modules function as a guide that organizes learning objectives, materials, activities and assessments, and can be adapted to student needs and available resources. This research involves creating teaching modules for TPQ Nurul Huda in Prayungan Hamlet, with a focus on preparing material that is practical and easy for children to understand. Activities begin with situation analysis, coordination with related parties, printing of modules, outreach to parents and teachers, and evaluation of module use. This program aims to improve the quality of religious learning, encourage parental involvement, and motivate children to learn. The results show an increase in children's interest and enthusiasm as well as positive support from parents, with the hope that this teaching module can become an effective reference for religious education in the future.